Utilization of thermophilic cellulolytic bacteria isolates and Trichoderma harzianum fungi on rice strow composting - Dini Mufriah; Rini Sulistiani (Syiah Kuala University, 2013)
The thermophilic cellulolytic bacteria are potential organisms for applications such as in decomposition of organic materials and enzyme technology. One potential organic materials which is very abundant in Indonesia is rice straw, which have not been optimally utilized. The problem is, the compostingprocess of straw in nature is used to take along time, so it needs to add effective decomposer microoroganisms which can adapt on compost termperature rise. The aims of this research were to isolated and selected thermophilic cellulolytic bacteria and Trichoderma harzianum and tested the isolates on rice straw composting. This research is executed in laboratory in faculty of agriculture, University of Alwashliyah Medan. Twenty thermophilic cellulolytic bacteria were isolated from several process composting of rice strawand corn waste at high temperature, from peat land and sidebu-debu hot spring, while Trichoderma harzianum fungi that used in this research was already got from previous research. Cellulolytic activity was determined by ability of bacteria and fungi to degrade carboxymethyl cellulose (CMC) substrate. Cellulolytic microorganisms was selected based on clear zone which form surrounding the colonies. Cellulase activity was measured by dinitrosalisilic acid (DNS) method. Results showed that there were 5 isolates (JG12, JG9,JG7 JR2, SD1) showing the best ability to degrade CMC. JG12 isolate had the higest diameter ratio of clear zone and enzyme activity ( 2,6 and 5,07 x 10-3 U/mL), while T. Harzianum had ratio of clear zone 1,22 and enzyme activity 4,02 x 10-3 U/mL).Then the selected bacteria and T. Harzianum were test on rice straw composting. This selection was used complete block Random Design Factorial, which consist of bacteria isolates as the first factor (S0=control, S1= Straw+JG7, S2=Straw+JR2, S3=Straw+JG9, S4=Straw+JG12, S5=Straw+SD1) and T. Harzianum as the second factor( T0=control, T1=Straw+T. harzianum). The result of this research are the highest decreasing of ratio C/N is caused by the treatment combination S4T1 which is consist of JG12 bacteria isolate that isolated from corn waste composting and Trichoderma harzianum (C/N = 17,16).